A Comparative Corpus-Based Study of Genitive Variation in Written Native and Non-Native Speakers’ Narratives - AFREH, ESTHER SERWAAH; OFOSU DWAMENA, DANIEL (International Journal of Language and Literary Studies, 2024)
This study investigates statistically significant factors impacting the choice between 's-genitive and of-genitive constructions and examines the interactions between these factors. Employing a mixed-method approach, we delve into whether native versus non-native speakers’ preferences motivate these influences. The analysis of the corpus aligns with previous studies, emphasizing different ways of indicating possession in language. Particularly, possessor animacy emerges as a significant factor influencing the choice between genitive variations, with animate possessors showing a bias towards the 's-genitive construction. Additionally, native speakers exhibit a higher preference for the 's-genitive in their narratives compared to non-native speakers. Structural weight and the concreteness or abstract nature of possessors also play a role in determining genitive form choice, with heavy possessors favouring the of-genitive construction and lighter possessors opting for the 's-genitive form. These findings hold true across both native and non-native speakers, indicating stability in genitive variation across first and second-language varieties of English. The study further uncovers differences between native and non-native speakers regarding the preference for concrete and abstract possessors in genitive constructions. Native speakers tend to favour abstract possessors in the 's-genitive, whereas non-native speakers lean towards concrete possessors, adding complexity to our understanding of genitive choice.